2009
DOI: 10.1038/laban0309-87
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between body weight changes and postoperative pain in rats treated with meloxicam or buprenorphine

Abstract: It is essential to identify objective and efficient methods of evaluating postoperative pain in rodents. The authors investigated whether postoperative changes in rates of body weight gain could serve as a measure of the efficacy of meloxicam or buprenorphine analgesia in growing rats. Young adult male Lewis rats underwent general endotracheal anesthesia and thoracotomy and were treated postoperatively for 3 d with saline (no analgesia), buprenorphine (six doses of 0.1 mg per kg) or meloxicam (three doses of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 25 publications
2
32
0
2
Order By: Relevance
“…Short term decreases in total weight and prolonged attenuation of weight gain rates are commonly observed after manipulation of rodents in experimental models of neuropathic and inflammatory pain [5; 8; 65; 68]. Consistent with those findings, we observed that bilateral DPI led to greater deficits in body weight relative to control animals.…”
Section: Resultssupporting
confidence: 90%
“…Short term decreases in total weight and prolonged attenuation of weight gain rates are commonly observed after manipulation of rodents in experimental models of neuropathic and inflammatory pain [5; 8; 65; 68]. Consistent with those findings, we observed that bilateral DPI led to greater deficits in body weight relative to control animals.…”
Section: Resultssupporting
confidence: 90%
“…Chronic i.c.v. For presumptive analgesia, meloxicam [1 mg/kg of body weight, s.c. (subcutaneously); Metacam ® ; Boehringer Ingelheim], a non-steroidal anti-inflammatory drug used for post-operative pain in rats [27], was administered immediately after surgery while the rats were still under anaesthesia and recovering on a temperature-regulated heating pad. Rats were anaesthetized with a ketamine cocktail (100 mg/ml ketamine; 5 mg/ml xylazine and 10 mg/ml acepromazine) and were placed in a stereotaxic frame.…”
Section: Experimental Designmentioning
confidence: 99%
“…The dose of meloxicam used in this study is substantially lower than reported in the literature 22 and was based on multimodal pain management experience in our veterinary academic teaching hospital with client-owned rodents. The dosages in the literature are based on unimodal analgesia in experimental pain with maximum effect.…”
Section: Discussionmentioning
confidence: 99%